PENGARUH PROGRAM MARKETING PUBLIC RELATIONS TERHADAP KEPUTUSAN PEMBELIAN MOBIL TYPE ERTIGA (Studi Kasus di Dealer Mobil Suzuki Ciledug) - Elah Elah (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2015)
This study aims to determine the effect of the product, promotion, price and place and the price ofpurchasing decicions at car type ertiga. The independen variable are product, promotion, price andplace affect the purchase decision as the dependen variable. The population in this study arecustomers dealer Suzuki Ciledug. Sample were taken of 50 respondents using a purposive samplingtechnique. Data was collected using a survey method through questionnaires filled out by customers.Then, the data obtained were analyzed using multiple regression analysis. This analysis include thevalidity test, reliability test, multiple regression analysis, classic assumption test, hypothesis testingthrough the F test and t test, and coefficient of determination analysis (R2). Based result, obtainedregression equation Y = 1,943 - 0,027X1 + 0,025X2 + 0,397X3+ 0,657X4. Based on statical dataanalysis, the indications in this research is valid and the variable are reliable. In testing theassumption of classical, regression model multikolonieritas, does not occur heterokedasitas, andnormal distribution. Individually, the variables have greater influence is product with the regressioncoefficient 0,027, followed by the promotion variable with a regression coefficient 0,025, price 0,397and promotion 0,657. The computation of hypothesis using the t test showed that the variable priceand place not significantly influence the purchase decision variable. Then through the F test can beknow that the independen variable is feasible to test variable of purchasing decision can be explainedby four independen variables in the regression quotation. The remaining 10,3% is explained by othervariable out side of the three variable used in this research.Key Word: Product, Price, Place, Promotion and Purchasing Decisions